Interaction between Flow Diverter and Parent Artery of Intracranial Aneurysm: A Computational Study. (25th October 2017) - Fu, Wenyu; Xia, Qixiao
Abstract : To evaluate the influence of deployment strategy on the mechanical interaction between braided stent and parent artery of intracranial aneurysm (the elasticity of the arterial wall is considered), finite-element analyses are carried out by referring to computational models of flow-diverter device and arterial wall. Two implantation strategies are used to virtually implant the braided stent into the ideal intracranial aneurysm model. One is the noncompacted implantation method, and the other is the implantation method of using push-pull technique. During the process of the implantation, the changes of the arterial shape around the aneurysm and the changes of the wall pressure at the contact area between the braided stent and the inner wall of the artery are analyzed. The results indicate that the average contact pressure in the area of low porosity is 57 mmHg using the push-pull technique, and the average contact pressure of the parent artery is 10.45 mmHg using the non-push-pull technique. The diameter of the parent artery at the aneurismal orifice increased about 0.2 mm when using the push-pull technique, so the elasticity of the vessel should be considered in the mechanical analysis of interaction between stent and vessel.